Neutropenia in adult acute myeloid leukemia patients represents a powerful risk factor for COVID-19 related mortality. Issue 8 (3rd July 2021) - Stahl, Maximilian; Narendra, Varun; Jee, Justin; Derkach, Andriy; Maloy, Molly; Geyer, Mark B.; Mato, Anthony R.; Roeker, Lindsey E.; Tallman, Martin S.; Shah, Gunjan L.; Daniyan, Anthony; Goldberg, Aaron D.
Abstract: Patients with hematological malignancies are at risk for poor outcomes when diagnosed with coronavirus disease 2019 (COVID-19). It remains unclear whether cytopenias and specific leukemia subtypes play a role in the clinical course of COVID-19 infection. Here, we report outcomes and their clinical/laboratory predictors for 65 patients with acute and chronic leukemias diagnosed with COVID-19 between 8 March 2020 and 19 May 2020 at Memorial Sloan Kettering Cancer Center in New York City. Most patients had CLL (38%) or AML (26%). A total of 14 (22%) patients required high flow nasal cannula or were intubated for mechanical ventilation and 11 patients (17%) died. A diagnosis of AML (OR 4.7, p =.028), active treatment within the last 3 months (OR 5.22, p =.047), neutropenia within seven days prior and up to 28 days after SARS-CoV-2 diagnosis (11.75, p =.001) and ≥3 comorbidities (OR 6.55, p =.019) were associated with increased odds of death.